2020
DOI: 10.1007/s10518-020-00998-7
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of relative-span ratio in rocking steel braced dual-frames

Abstract: Controlled rocking concentrically steel braced frame (CR-CSBF) is an earthquake-resisting system that is effectively capable of reducing structural damage after earthquakes and causes resilience in the structure. Post-tensioning (PT) strands and fuse members are two important elements in CR-CBSFs to provide frame self-centering and energy dissipation, respectively. This study firstly purposes to evaluate the nonlinear response history analysis with five different relative-span ratios (A/B = 1.5, 2.0, 2.5, 3.0,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…It was observed that by suspending the oors, not only does the energy dissipation increase [11], but also the suspended oors act as tuned mass dampers (TMDs) which protect the structures from progressive collapse, explosions, and ground motions [12]. Low-damage systems are not limited to concrete shear walls only; Rather, they have been widely used in the construction industry with different materials and speci cations to improve buildings' performance such as cross-laminated timber [13,14], steel braced [15], masonry [16], and in lled rocking shear walls [17]. These systems can also be implemented in different types of structures like bridges to isolate the main deck from piers and therefore, leading to a dramatic decrease in relative displacements [18].…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that by suspending the oors, not only does the energy dissipation increase [11], but also the suspended oors act as tuned mass dampers (TMDs) which protect the structures from progressive collapse, explosions, and ground motions [12]. Low-damage systems are not limited to concrete shear walls only; Rather, they have been widely used in the construction industry with different materials and speci cations to improve buildings' performance such as cross-laminated timber [13,14], steel braced [15], masonry [16], and in lled rocking shear walls [17]. These systems can also be implemented in different types of structures like bridges to isolate the main deck from piers and therefore, leading to a dramatic decrease in relative displacements [18].…”
Section: Introductionmentioning
confidence: 99%